2016
DOI: 10.1245/s10434-016-5268-2
|View full text |Cite
|
Sign up to set email alerts
|

Do LORIS Trial Eligibility Criteria Identify a Ductal Carcinoma In Situ Patient Population at Low Risk of Upgrade to Invasive Carcinoma?

Abstract: Background The Surgery versus Active Monitoring for Low-Risk DCIS (LORIS) trial is studying the safety of monitoring core-biopsy diagnosed low-risk ductal carcinoma in situ (DCIS) without excision. We sought to determine the incidence and characteristics of synchronous invasive carcinoma found in LORIS-eligible women who underwent excision, as this knowledge is essential in assessing the safety of observation alone. Methods Women meeting LORIS eligibility criteria (age ≥ 46 years, screen-detected calcificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 26 publications
3
37
1
Order By: Relevance
“…7 Such non-operative management should not be attempted outside of a clinical trial, as recent work by Pilewskie showed that among women with DCIS who met LORIS eligibility requirements on core biopsy, 20% had invasive cancer found in the surgical excision specimen that was heterogeneous in grade, size, and receptor status. 22 Further, among women with DCIS who continued to meet LORIS criteria even after examination of the complete surgical excision specimen, the 10-year IBE rate was a substantial 12.1%. 23 Our current data show that in our entire population of women with very low-volume DCIS, and in the subsets of those age ≥50 years and those with low-grade DCIS, risk of IBE was clinically significant at 10-years: 12.3% (entire population), 12.6% (age ≥50 years), and 14.6% (low grade, including cases borderline between ADH and DCIS), respectively.…”
Section: Discussionmentioning
confidence: 95%
“…7 Such non-operative management should not be attempted outside of a clinical trial, as recent work by Pilewskie showed that among women with DCIS who met LORIS eligibility requirements on core biopsy, 20% had invasive cancer found in the surgical excision specimen that was heterogeneous in grade, size, and receptor status. 22 Further, among women with DCIS who continued to meet LORIS criteria even after examination of the complete surgical excision specimen, the 10-year IBE rate was a substantial 12.1%. 23 Our current data show that in our entire population of women with very low-volume DCIS, and in the subsets of those age ≥50 years and those with low-grade DCIS, risk of IBE was clinically significant at 10-years: 12.3% (entire population), 12.6% (age ≥50 years), and 14.6% (low grade, including cases borderline between ADH and DCIS), respectively.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study by Pilewskie et al evaluated 296 LORIS-eligible patients diagnosed with DCIS by core needle biopsy between 2009 and 2012; of these, 20% had invasive carcinoma at surgical excision that was heterogeneous in grade, size, and receptor status (51). Therefore, until further risk stratification can identify patients who may be at low risk for upgrade to invasive carcinoma, patients with core biopsy-proven DCIS should not be considered for observation outside of a clinical trial.…”
Section: Prospective Studies Of Observation In Low-risk Dcismentioning
confidence: 99%
“…However, unlike our results, a recent study of 296 patients who met criteria for the LORIS trial identified up to 58 patients with invasive carcinoma upon excision, emphasizing that there is a risk when including patients with pure DCIS on core biopsy because of undersampled invasive carcinoma, despite strict inclusion and exclusion criteria. 32 In summary, approximately one-half the upgrades in our study were due to low-and intermediate-grades of DCIS; therefore, this diagnosis of DCIS on core biopsy should not be underassumed or underestimated as being an indolent lesion. Axillary lymph node positivity was rare but affected 3% (7 of 218) of the carcinomas smaller than 2 cm.…”
Section: Discussionmentioning
confidence: 55%